2016
DOI: 10.1097/mib.0000000000000855
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review on Infliximab and Adalimumab Drug Monitoring

Abstract: Concerning drug levels monitoring any methodology is adequate. With respect to antidrug antibody levels, it will be necessary to define a gold standard method or to establish different cutoff levels for different methodologies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 46 publications
0
26
0
Order By: Relevance
“…ATIs measurement can also be performed using fluid-phase radioimmunoassay and homogeneous mobility shift assay (HMSA), which are reportedly more precise. However, a gold standard measurement method and corresponding optimal cut-off levels for each method have not yet been established [4]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ATIs measurement can also be performed using fluid-phase radioimmunoassay and homogeneous mobility shift assay (HMSA), which are reportedly more precise. However, a gold standard measurement method and corresponding optimal cut-off levels for each method have not yet been established [4]. …”
Section: Discussionmentioning
confidence: 99%
“…Several IFX cut-off levels for predicting remission have been reported. Higher levels are associated with remission defined by low C-reactive protein (CRP) levels [4] and fistula healing [5]. According to a recent study, lower IFX levels and higher faecal calprotectin (CPT) can be used to predict relapse in adult populations [6].…”
Section: Introductionmentioning
confidence: 99%
“…Optimizing therapy during the induction phase so that IFX or ADM concentrations are kept above certain thresholds has proven to be associated with improved responses and better outcomes (13) in IBD. Despite their overall therapeutic efficacy, more than one-third of patients on TNF-α inhibitors show no response to induction therapy (primary nonresponders) and in up to 50% of the responders, therapy becomes ineffective over time (secondary nonresponders) (1416).…”
Section: Why Measure Therapeutic Mabs In the Clinical Laboratorymentioning
confidence: 99%
“…Laboratory testing of patients for quantitation of the MAb concentrations in circulation and assessment of immunogenicity can help optimize therapy when a partial response or a loss of response to therapy is observed. Results from laboratory testing play an important role in patient management, considering the evidence accrued for the TNF-α inhibitor class in IBD (13, 14, 1720). When trough levels are measured in patients who have undetectable or low concentrations of the MAb but no detectable ADAs, the physician may choose to increase the dose of the MAb in an attempt to increase the amount of the drug in circulation.…”
Section: Why Measure Therapeutic Mabs In the Clinical Laboratorymentioning
confidence: 99%
“…Studies have continuously shown there is benefit in having laboratory tests to quantify mAbs as part of routine care. Concentrations of infliximab or adalimumab above certain thresholds result in improved responses to therapy and better outcomes when compared to empirical trial and error, and thus, success is keeping the patient on mAbs for as long as possible (7).…”
Section: Laboratory Reflectionsmentioning
confidence: 99%